Paradigm shift or business as usual? workers’ views on multi-stakeholder initiatives in Bangladesh - Kabeer, Naila; Huq, Lopita; Sulaiman, Munshi (Wiley Online Library, 2022)
This article was published in Development and Change [© 2020 The Authors. Development and Change published by John Wiley & Sons Ltd on behalf of International Institute of Social Studies] and the definite version is available at: https://doi.org/10.1111/dech.12574 The Article's website is at: https://onlinelibrary.wiley.com/doi/10.1111/dech.12574